PILIHAN BAHASA MASYARAKAT MULTILINGUAL DI KOTA SAMPIT (THE LANGUAGE CHOICE OF A MULTILINGUAL COMMUNITY IN SAMPIT CITY) - Trisnawati Trisnawati (Universitas Lambung Mangkurat, 2023)
Â AbstractThe Language Choice of A Multilingual Community in Sampit City. This study aims to describe the form of language choice of multiethnic communities in Sampit City in the realm of family, friendship, religion, education, and employment, and the factors that influence the language choice of multiethnic communities in Sampit City. This study used qualitative approach with field research. The method that was used in this study was descriptive method. Based on the results of the study, it can be concluded that there are various languages that coexist in a multilingual community in Sampit, namely Indonesian, Dayak, Banjar, Javanese, Maduranese, Bima, Batak, and Serawai. The dominant language used besides Indonesian is Banjar, because it is considered to have the highest prestige, so it is often chosen in communication. Multilingual people in Sampit are able to use language for the purpose of communication or polyglossia, and are able to distinguish between high and low varieties or diglossia. The choice of language made by the multilingual community in Sampit is influenced by the factors of people (participants), topics and situations.Keywords:Â language choice, speech community, multilingual.AbstrakPilihan Bahasa Masyarakat Multilingual di Kota Sampit. Penelitian ini bertujuan untuk mendeskripsikan wujud pilihan bahasa masyarakat multilingual di Kota Sampit pada ranah keluarga, kekariban, agama, pendidikan, dan lapangan kerja, dan faktor yang memengaruhi pilihan bahasa masyarakat multilingual di Kota Sampit. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan. Metode yang digunakan adalah metode deskriptif. Berdasarkan hasil penelitian, dapat disimpulkan bahwa terdapat berbagai bahasa yang hidup berdampingan di tengah masyarakat multilingual di Kota Sampit, yaitu bahasa Indonesia, bahasa Dayak, bahasa Banjar, bahasa Jawa, bahasa madura, bahasa Bima, bahasa Batak, dan Serawai. Bahasa yang dominan digunakan selain bahasa Indonesia adalah bahasa Banjar, karena dianggap memiliki prestise tertinggi, sehingga sering dipilih dalam komunikasi. Masyarakat multilingual di Kota Sampit mampu menggunakan bahasa dengan tujuan komunikasi atau poliglosia, dan mampu membedakan ragam tinggi dan ragam rendah atau diglosia. Pilihan bahasa yang dilakukan oleh masyarakat multilingual di Kota Sampit dipengaruhi oleh faktor orang (partisipan), topik dan situasi.Kata-kata kunci: pilihan bahasa, masyarakat tutur, multilingual